1993
DOI: 10.1111/j.1360-0443.1993.tb02117.x
|View full text |Cite
|
Sign up to set email alerts
|

Punishment as a factor in preventing alcohol‐related accidents

Abstract: As a humanitarian and economic 'bad', infliction of punishment requires justification in terms of compensating achievements, as well as moral appropriateness. In the context of road accidents, there is evidence that increasing the certainty and swiftness of threatened punishment may deter risky behavior, although increasing the severity of the threat seems ineffective. These effects may be generalizable to other kinds of accidents, but empirical evidence is lacking. A further possibility for the justifiable us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…As a result, the National Police was able to expand its repertoire of traffic control strategies since a whole new array of road risky behaviours could be addressed. Second, we observed that, as some literature had suggested,11 12 traffic law reforms can be sterile if these instruments are not supported by other actions. In this particular case, we actually notice that the traffic law reform did not have a significant independent impact on traffic fatalities or severe injuries for the 2000–2012 period.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As a result, the National Police was able to expand its repertoire of traffic control strategies since a whole new array of road risky behaviours could be addressed. Second, we observed that, as some literature had suggested,11 12 traffic law reforms can be sterile if these instruments are not supported by other actions. In this particular case, we actually notice that the traffic law reform did not have a significant independent impact on traffic fatalities or severe injuries for the 2000–2012 period.…”
Section: Discussionmentioning
confidence: 78%
“…While a vast literature suggests that road traffic legislation reforms per se may help to prevent the occurrence of traffic crashes and its consequences,3–10 others have argued that this type of measure is ultimately sterile or at best short-lived 11 12. The latter has been particularly noticeable in Latin American countries since in many cases they lack the necessary resources to implement legislative changes 13–15.…”
Section: Introductionmentioning
confidence: 99%
“…More effective is swift and certain punishment such as disqualification from driving after failing a breath test or refusing to submit to a test (208). There is also evidence Relative risk of driver involvement in police-reported crashes Source: references 195, 199-201. that requiring high-risk offenders (those with BAC exceeding 0.15 g/dl) to take driver rehabilitation courses can reduce the rate of repeat offences (186,209).…”
Section: Enforcing Blood Alcohol Concentration Limits and Publicizingmentioning
confidence: 99%
“…How to deploy limited law enforcement resources to maximal effect is one of the central questions of law and economics. One perspective advocates intense, preannounced crackdowns, to take advantage of assumed increasing returns of arrest probabilities on criminal activity (Eeckhout, Persico and Todd, 2010;Ross, 1993) . Others argue that unless it is possible to police all locations all the time, the deployment should be randomized over time and across the potential locations where the wrongdoing could take place, because otherwise the wrongdoers would simply switch to the unpoliced locations and continue their activities with impunity (Clarke and Weisburd, 1994;Mookherjee and Png, 1994) Date: First Draft August 4, 2013.…”
Section: Introductionmentioning
confidence: 99%